Abnormal Spontaneous Brain Activity in Women with Premenstrual Syndrome Revealed by Regional Homogeneity - Liao, Hai; Pang, Yong; Liu, Peng; Liu, Huimei; Duan, Gaoxiong; Liu, Yanfei; Tang, Lijun; Tao, Jien; Wen, Danhong; Li, Shasha; Liang, Lingyan; Deng, Demao (Frontiers in Human Neuroscience, 2017)
Abstract Background: Previous studies have revealed that the etiologies of premenstrual syndrome (PMS) refer to menstrual cycle related brain changes. However, its intrinsic neural mechanism is still unclear. The aim of the present study was to assess abnormal spontaneous brain activity and to explicate the intricate neural mechanism of PMS using resting-state functional magnetic resonance imaging (RS-fMRI). Materials and Methods: The data of 20 PMS patients (PMS group) and 21 healthy controls (HC group) were analyzed by regional homogeneity (ReHo) method during the late luteal phase of menstrual cycle. In addition, all the participants were asked to complete a daily record of severity of problems (DRSP) questionnaire. Results: Compared with HC group, the results showed that PMS group had increased ReHo mainly in the bilateral precuneus, left inferior temporal cortex (ITC), right inferior frontal cortex (IFC) and left middle frontal cortex (MFC) and decreased ReHo in the right anterior cingulate cortex(ACC) at the luteal phase. Moreover, the PMS group had higher DRSP scores, and the DRSP scores positively correlated with ReHo in left MFC and negatively correlated with ReHo in the right ACC. Conclusion: Our results suggest that abnormal spontaneous brain activity is found in PMS patients and the severity of symptom is specifically related to the left MFC and right ACC. The present findings may be beneficial to explicate the intricate neural mechanism of PMS.